Cloning and Expression of Recombinant Human Epidermal Growth Factor In Escherichia Coli - Abdull Razis, Ahmad Faizal (2007)
The expression of recombinant hEGF (human epidermal growth factor) in Escherichia coli was conducted to produce hEGF with free of inclusion bodies and biologically active. The recombinant hEGF was constructed using sticky ends ligation and resulted in successful insertion of the hEGF gene into the multiple cloning sites of the pFLAG-ATS. This insertion was confirmed by restriction enzyme analysis, PCR (polymerase chain reaction) and DNA (deoxyribonucleic acid) sequencing with 100% homology. The recombinant hEGF was expressed in E. coli at 2, 4 and 6 hours with induction of 0.5 mM and 1.0 mM IPTG (isopropylthiogalactopyranoside).This recombinant was found to be expressed as periplasmic fraction and whole cell insoluble fraction as confirmed with SDS-PAGE (sodium dodecyl sulphate-polyacrylamide gel electrophoresis) and western blotting analyses. These analyses showed the molecular weight of hEGF was approximately 6.8 kDa. There was no significant difference in the production of hEGF when the expression was induced with different IPTG concentration; however, for each IPTG concentration, there was significant difference between 0 hour and all the post-induction hours. In addition, hEGF was found to be significantly higher in periplasmic fraction as compared to the whole cell insoluble fraction (196.5 ng/ml as compared with 167 ng/ml at 2 hour, 175.7 ng/ml as compared with 115.3 ng/ml at 4 hour and 168.3 ng/ml as compared with 140 ng/ml at 6 hour). Growth-stimulating activity of periplasmic hEGF was studied using BrdU (bromodeoxyuridine) cell proliferation assay and MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide) cell proliferation assay. The periplasmic hEGF as compared to the standard hEGF was found to be biologically active and showed similar activity. There were significant findings of periplasmic hEGF in stimulating the growth of HEK (human epidermal keratinocytes) at 24, 48 and 72 hours of incubation. Even at the highest concentration of periplasmic hEGF (10 ng/ml), the growth-stimulating activity still occurred and incubation at 48 hour resulted with the highest stimulation (85.4% at 10 ng/ml, 77.7% at 1 ng/ml, 70.7% at 0.1 ng/ml, 55.9% at 0.01 ng/ml and 37.6% at 0.001 ng/ml). Besides, MTT cell proliferation assay of periplasmic hEGF on HDF (human dermal fibroblasts) showed significant increased in the growth-stimulating activity when the duration of incubation increased. Highest percentage of HDF growth was found at 72 hour incubation as compared with 24 and 48 hours incubation. In conclusion, the findings showed recombinant hEGF was successfully expressed in E. coli and the growth-stimulating activity of hEGF was determined.